The redistribution of trade gains and the equity-efficiency trade-off - Marco de Pinto (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2012)
The contribution of this paper is to derive an optimal redistribution scheme for trade gains in the case of a government's objective function that explicitly accounts for the equity-efficiency trade-off. The government pays unemployment benefits (UB) either financed by a wage tax, a payroll tax or a profit tax paid by exporters only. Using a Melitz-type framework with unionized labor markets and heterogeneous workers we show that there is a clear-cut ranking of the redistribution schemes in terms of welfare level: 1. UB financed by a profit tax paid by exporters, 2. UB financed by a wage tax, 3. UB financed by a payroll tax.
Keywords: F1; F16; H2; 330; trade liberalization; heterogeneous firms; trade unions; income inequality; unemployment benefits; taxes; Handelsliberalisierung; Außenhandelsgewinn; Arbeitslosenversicherung; Einkommensumverteilung; Ertragsbesteuerung; Exportwirtschaft; Theorie